Dangdut Music as a Realization of Indonesian Cultural Diplomacy and Social Relations Between Countries - Akmal, Mochamad; Argenti, Gili; Marsingga, Prilla (Peneliti.net, 2024)
Music is a means of cultural diplomacy that has become the center of scientific attention around the world. This study aims to describe the Indonesian government's efforts to strengthen cultural diplomacy on international scale through dangdut music which is assisted by the development of the digital age, namely through TV programs and sports tournaments throughout Asia. Dangdut Academy Asia and the Asian Games are one of the means to promote dangdut on the international scene, especially Asia. The theory of popular culture and cultural diplomacy is used in this study to explain how dangdut music packaged in TV programs can influence people's lives in a positive way.